A needs assessment of community pharmacists for pharmacist specialization in Canada. (4th August 2016) - Jorgenson, Derek; Penm, Jonathan; MacKinnon, Neil; Smith, Jennifer
Abstract: Objectives: Pharmacists are increasingly providing specialized services. However, no process exists for specialist certification in Canada. The aim of this study was to determine the extent to which Canadian community pharmacists support the development of a certification system for specialization. Methods: This study utilized a cross-sectional online survey of licensed Canadian pharmacists identified through the member databases of national and regional pharmacy associations. A questionnaire was developed (in French and English) and distributed via email, on behalf of the researchers, by multiple pharmacy organizations in January 2015. Multivariate logistic regressions were conducted to identify which sub-groups of respondents supported the creation of a certification system and which supported mandatory certification. Key findings: A total of 770 responses were received. Many respondents were practising specialists (30.0%, 205/683) and the most commonly reported specialty areas were diabetes, smoking cessation and geriatrics. Almost 85% ( n = 653/770) supported creation of a Canadian certification process and 68.5% ( n = 447/653) felt certification should be mandatory. Respondents believed that the primary benefit of a certification system was greater public confidence in pharmacist specialist skills. They also felt that the most important factor in the development of the system is to create national definitions for specialty practice. The main barrier was the lack of reimbursement for specialty services in Canada. Conclusions: The majority of Canadian community pharmacist respondents support the creation of a certification process for pharmacist specialization. Future study is required to confirm this finding in a larger sample and to determine the optimal model and the financial feasibility of a national system in Canada.